Evaluating the mitigating potential of tourism on economic growth-induced ecological footprint: Insights from Asian countries - Bin Guo (Heliyon)
Over the past three decades, Asian countries have experienced rapid economic growth, leading to a substantial increase in ecological footprint and posing significant challenges to sustainability. This study investigates the potential of tourism as a sustainable development strategy to mitigate the ecological footprint induced by economic growth. Utilizing data from 1990 to 2022 across 28 Asian countries, rigorous econometric methods including panel cointegration tests were employed to detect co-integration relationships. The results not only confirm the existence of co-integration but also reveal that tourism plays a crucial role in reducing the ecological footprint associated with economic growth in Asian countries. Furthermore, the study identifies specific mechanisms through which tourism contributes to mitigating environmental impact, such as promoting sustainable practices, conservation efforts, and eco-friendly infrastructure development. These findings underscore the importance of integrating tourism into sustainable development strategies and highlight its potential to balance economic growth with environmental conservation in Asian nations. This research provides actionable insights for policymakers and stakeholders, emphasizing the need for sustainable tourism initiatives to address the challenges of economic growth-induced ecological footprint in Asia.